Social support in people, that live with HIV in Lima - Fasce Cayo, Ninoshka (2001)
This research studies the social support in a group of adult persons with HIV: 14 women and 41 men between 18 and 58 years of age, from medium- low social economic status that appeal to state health centers, non government entities and mutual support groups of Lima. The resultsof perceived social support, effective social support, social support satisfaction and social support need ha ve been correlated with variables age, sex, diagnostic time, presence of symptoms associated lo H!V, participation in a mutual support group, sex and sexual orientation(heterosexual males, men that have sex with other men and heterosexual women).The results showed that the social support indexes behaved differently according to weather they participated in a mutual support group or not, according to sex, according to sex and sexual orientation. Also, the need for social support rate varies according to diagnostic time.